The Effect of Insect Flour on The Growth Media of Beauveria bassiana in Controlling the Pupa Stage of Bactrocera carambolae - Choerunnisa, Agustya Salma; Rahmadhini, Noni; Windriyanti, Wiwin (BIOEDUSCIENCE, 2025)
Background: One effective method for controlling Bactrocera carambolae is the use of Beauveria bassiana. However, a common challenge is the decline in the conidial quality and virulence due to the lack of chitin and protein sources. The insect Tenebrio mollitor and the pupal casings of Hermetia illucens are rich in chitin and have the potential to enhance the growth medium. Methods: The study used RAKF consisting of 3 factors and 3 replications. The first factor was the Type of Flour (T) consisting of T1: T. mollitor and T2: H. illucens. The second factor was Flour Concentration (K), which consisted of K1: 0.5% K2: 1% and K3: 1.5%. The third factor was Drying Temperature (S), of S1: 1000C S2: 1100C and S3: 1200C. Results: The results of the study show that the treatment caused symptoms of infection in the form of mycelium growth on the pupal cuticle and abnormalities in the emergence imago. The best combination is T2K2S2 (1% H. illucens flour at 1100C) which gives a mortality rate up to 76.7%, pupal duration of 9.3 days, and viability rate of 92.2%. Conclusions: The combination of H. illucens flour at a concentration of 1% and a drying temperature of 1100C is quite effective in increasing the ability of B. bassiana in controlling B. carambolae pupae in vitro.